Use of spice extracts and its impact on lipid profile in vivo - Jorge, N. [UNESP]; Veronezi, C. M. [UNESP]; Del Re, P. [UNESP] (Univ Putra Malaysia Press, 2016)
This study aimed to evaluate the antioxidant and hypolipemiant effect of oregano and thyme oleoresins under the lipid profile and the oxidation of the LDL fraction in vivo. Wistar rats were used and fed with a hypercholesterolemic diet and oleoresin supplementation by gavage, for 40 days. Analyses of the lipid profile and LDL oxidation were performed. The isolated administration of oleoresins significantly reduced the values of total cholesterol when compared to the group that received only the hypercholesterolemic diet. The supplementation with oregano oleoresin was the most effective one, regarding the reduction of total cholesterol. (C) All Rights Reserved
Keywords: Oreganum vulgar L.; Thymus vulgaris L.; Rats; Supplementation